Two-Dimensional Periodic Nanostructure Fabricated on Titanium by Femtosecond Green Laser - Yi-Hsien Liu; Shu-Chun Yeh; Chung-Wei Cheng (Nanomaterials, 2020)
Laser-induced periodic surface structures (LIPSS) is the sub-wavelength periodic nanostructure, which is generally generated by the femtosecond laser. There are two kinds of LIPSS, low spatial frequency LIPSS (LSFL) and high spatial LIPSS (HSFL), and the period size is close and less than half of the laser wavelength, respectively. Fabrication of two-dimensional (2D) LSFL and HSFL on a titanium surface with a linear-polarized femtosecond green laser beam (wavelength 515 nm) and cross-scanning strategies is demonstrated in this study. Four types of LIPSS structures are obtained by controlling the laser fluence, irradiated pulses, and cross-scanning strategies: 1D-LSFL perpendicular to laser polarization with a period of 300–360 nm, 1D-HSFL parallel to laser polarization with a period of 55–75 nm, 2D-LSFL dot-like structures with a period ~200 nm, and 2D-HSFL net-like structures with a period of 50–100 nm.